FAKTOR-FAKTOR PSIKOSOSIAL PADA TENAGA KESEHATAN DI MASA SEBELUM DAN SAAT PANDEMI COVID-19 - Ageng Priambudi; Dadan Erwandi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The World Health Organization (WHO) has declared the COVID-19 outbreak a public health emergency of international concern (PHEIC) and officially designated as a pandemic outbreak and health workers are the frontline workers in diagnosing and providing care to patients infected with COVID-19. Stress is a form of psychosocial risk, namely a physical and mental response due to an imbalance between demands and abilities. The purpose of this study is to look at Psychosocial Factors in Health Workers in the period before and during the COVID-19 Pandemic. This study used the Preferred Reporting Items for Systematic Reviews & Meta-Analysis (PRISMA) method systematically. The inclusion criteria in the study included using original studies related to topics published during the COVID-19 pandemic in 2020-2021 while before the COVID-19 pandemic published in 2017-2019, and open access to studies. Factors changes that occur in health workers on psychosocial factors involved before and during the pandemic, including age, gender, job demands, marital status, organizational roles, interpersonal relationships and leadership, and fear of COVID-19 infection. The COVID-19 pandemic has brought changes to the work system of health workers, of course, this affects the psychosocial aspects of health workers. In addition, the COVID-19 pandemic has also brought changes to the psychosocial factors that exist in health workers when compared to before the pandemic. Keywords: Associated factors, Psychosocial Factors, health care workers, COVID-19 pandemic